Alleviating nitrogen and phosphorus limitation does not amplify potassiuminduced increase in terrestrial biomass - Liang,G; Sun,P; Waring,BG; Fu,Z; Reich,PB (Global Change Biology, 2025)
Potassium (K) is the second most abundant nutrient element in plants after nitrogen (N), and has been shown to limit aboveground production in some contexts. However, the role of N and phosphorus (P) availability in mediating K limitation in terrestrial production remains poorly understood; and it is unknown whether K also limits belowground carbon (C) stocks, which contain at least three times more C than those aboveground stocks. By synthesizing 779 global paired observations (528, 125, and 126 for aboveground productivity, root biomass, and soil organic C [SOC], respectively), we found that K addition significantly increased aboveground production and SOC by 8% and 5%, respectively, but did not significantly affect root biomass (+9%). Moreover, enhanced N and/or P availability (through N and P addition) did not further amplify the positive effect of K on aboveground productivity. In other words, K had a positive effect on aboveground productivity only when N and/or P were limiting, indicating that K could somehow substitute for N or P when they were limiting. Climate variables mostly explained the variations in K effects; specifically, stronger positive responses of aboveground productivity and SOC to K were found in regions with high mean annual temperature and wetness. Our results suggest that K addition enhances C sequestration by increasing both aboveground productivity and SOC, contributing to climate mitigation, but the positive effects of K on terrestrial C stocks are not further amplified when N and P limitations are alleviated.